Changing Work and Work-Family Conflict: Evidence from the Work, Family, and Health Network. (June 2014) - Kelly, Erin L.; Moen, Phyllis; Oakes, J. Michael; Fan, Wen; Okechukwu, Cassandra; Davis, Kelly D.; Hammer, Leslie B.; Kossek, Ellen Ernst; King, Rosalind Berkowitz; Hanson, Ginger C.; Mierzwa, Frank; Casper, Lynne M.
Schedule control and supervisor support for family and personal life may help employees manage the work-family interface. Existing data and research designs, however, have made it difficult to conclusively identify the effects of these work resources. This analysis utilizes a group-randomized trial in which some units in an information technology workplace were randomly assigned to participate in an initiative, called STAR, that targeted work practices, interactions, and expectations by (1) training supervisors on the value of demonstrating support for employees' personal lives and (2) prompting employees to reconsider when and where they work. We find statistically significant, although modest, improvements in employees' work-family conflict and family time adequacy, and larger changes in schedule control and supervisor support for family and personal life. We find no evidence that this intervention increased work hours or perceived job demands, as might have happened with increased permeability of work across time and space. Subgroup analyses suggest the intervention brought greater benefits to employees more vulnerable to work-family conflict. This study uses a rigorous design to investigate deliberate organizational changes and their effects on work resources and the work-family interface, advancing our understanding of the impact of social structures on individual lives.